Sky-blue phosphorescent organic light-emitting diode with superior performance based on novel chlorine functionalized iridium(III) complex. Issue 21 (23rd May 2018) - Gao, Long; Tao, Peng; Miao, Yanqin; Jia, Wei; Zhao, Yaping; Wang, Hua; Xu, Bingshe
Graphical abstract: Highlights: Chlorine functionalized phosphorescent neutral Ir(III) phosphor has been designed. Novel phosphor with robust Caryl -Cl bond shows sky-blue emission with high Φ PL . High-performance sky-blue OLED have been successfully fabricated. Abstract: A novel and highly efficient chlorine functionalized iridium(III) complex is designed and synthesized. The complex shows intensive sky-blue phosphorescence (with a peak of 492 nm and a shoulder at 524 nm), high photoluminescence efficiency (0.78) and moderate full width at half maximum (62 nm). The aromatic chlorine introduced into the complex provides the robust chemical stability and effective sky-blue phosphorescence for organic light-emitting diodes (OLEDs). The maximum power efficiency, current efficiency and external quantum efficiency for the complex based OLED are up to 48.46 lm/W, 55.04 cd/A and 18.47%, respectively.